Impact of treated wastewater reuse in agriculture on the transfer of antimicrobial-resistant bacteria and genes to edible crops: a One Health perspective - Gomes, Anicia; López-Cañizares, Jesús; Moreno-Candel, Macarena; Martinez-Alonso, Alberto; Allende, Ana; Truchado, Pilar (Frontiers in Microbiology, 2026)
This study evaluated whether irrigation with treated wastewater of different microbiological quality (secondary- and tertiary-treated wastewater) contributes to the transmission of antibiotic-resistant bacteria (ARB) and antimicrobial resistance genes (ARGs) from irrigation water to lettuce plants, using potable water as control. Bacterial indicators (Escherichia coli and extended-spectrum β-lactamase-producing E. coli, ESBL-E. coli) and ARGs (blaCTX–M–1, blaTEM, sul1, tetA) were quantified in irrigation water and lettuce using culture-based methods and quantitative PCR (qPCR). In addition, the efficiency of tertiary treatment in reducing Escherichia coli, ESBL-E. coli, and resistance genes in reclaimed water was assessed. The relative abundance of ARGs was normalized to the 16S rRNA gene to evaluate potential amplification or persistence of resistance during water reuse and irrigation. Results showed that E. coli and ESBL-E. coli were consistently detected in crops irrigated with secondary-treated water but remained below detection limits after irrigation with tertiary-treated and potable water. Resistance gene profiles followed a similar trend: secondary-treated water contained the highest absolute and relative abundances of blaCTX–M–1, blaTEM, sul1, and tetA, while tertiary treatment substantially reduced but did not completely eliminate them. In lettuce, ARG levels on lettuce were substantially lower than in the corresponding irrigation waters, representing only 4 and 6% of the concentrations detected in tertiary- and secondary-treated wastewater, respectively. This reduction indicates limited transfer and/or persistence of ARGs on the plant surface despite detectable levels in the irrigation water. Our study provides valuable insights into the role of poor-quality irrigation water in driving ARGs dissemination to fresh produce and shows that advanced tertiary treatments significantly reduce AMR-related risks, thereby supporting the safe and sustainable use of reclaimed water in agriculture.